Habilidades auditivas e análise neurofisiológica da codificação neural em crianças com transtorno fonológico - Rohers, Dara Eliza (2024)
Speech production involves cortical and subcortical sensory and motor networks in the brain, integrating auditory information, representing sounds, and planning motor execution to produce speech sounds. Thus, in addition to auditory sensitivity, it is essential to effectively interpret received auditory information to develop speech perception and, consequently, speech production. Therefore, this work aimed to investigate auditory skills, auditory behavior, and neural encoding in children with phonological disorder (PD). This is a cross-sectional, analytical, and quantitative study. A total of 28 subjects between the ages of five and 11 participated in the research, divided into two groups: Study Group (SG), consisting of 13 children with a previous diagnosis of PD, and Control Group (CG), consisting of 15 children with typical speech development/acquisition. All participants underwent basic audiological evaluation, evaluation of auditory figure-ground skills through the administration of the Dichotic Digits Test (DDT) – binaural integration stage, and temporal resolution evaluated through the Random Gap Detection Test (RGDT). Parents and/or guardians answered the Auditory Processing Domains Questionnaire (APDQ) regarding their children's auditory behavior. In addition, neural encoding of speech sounds was analyzed through the recording and analysis of the Frequency Following Response (FFR), with analysis of amplitudes, absolute latencies (ms) (V, A, C, D, E, F, and O), displacements (ms) (V-D, C-D, D-O, A-D, and A-O), and measurement of slope (ms/μV). A qualitative analysis of the FFR was also performed using the time-frequency distribution (TFD) of the Spectrogram, available through the equipment's software. Inferential analysis of the data was performed. Regarding the behavioral evaluation of auditory skills, a statistically significant difference was observed in the responses of the DDT behavioral test, indicating that children with PD are highly likely to have an alteration in the auditory figure-ground skill. Although numerically, children with PD have a higher occurrence of alteration in temporal resolution auditory skill, no statistical difference was observed. In both groups, parents reported concerns about their children's auditory behavior. Regarding the neural encoding of speech sounds, there was no statistically significant difference between the evaluated groups in terms of amplitude. As for the analysis of the time domain (ms), although numerically, most latency values of the different components of the FFR in SG are higher than in CG, statistically, children in SG had a higher latency value only in component O compared to CG. Regarding displacements, the A-O displacement was higher for SG compared to CG. The other displacement and slope results were not influenced by the evaluated group. No correlation between behavioral tests and latency results was observed. Conversely, a positive correlation between the severity of SSD and the latency of component E was observed, indicating that the more severe the disorder, the higher the latency of E. The analysis of TFD allowed for the observation of differences when comparing the electrophysiological-neurophysiological responses of one subject from CG and one subject from SG. It was possible to investigate auditory skills, auditory behavior, and neural encoding of speech sounds in children with PD. The most clinically relevant finding is that in children with atypical speech, the auditory figure-ground skill is more likely to be altered.